HUBUNGAN PENGETAHUAN DENGAN SIKAP TENAGA BASIC LIFE SUPPORT DI PUSKESMAS PANCURBATU KABUPATEN DELISERDANG - Lilis Novitarum; Siti Meilan Simbolon (Elisabeth Health Jurnal, 2017)
Knowledge and attitudes are the result of out through a specific sensing of objects and social interaction so that the formation of a person's actions. Basic Life Support was given an early intervention in the treatment of patients in cardiac arrest (cardiac arrest). Goal : This study aimed to analyze the relationship between knowledge with attitude of health workers on basic life support in Puskemas Pancur Stone Deli Serdang. Methods: The method used is descriptive analytic research with cross sectional approach. Samples numbered 32 with a sampling technique is total sampling. Measuring instrument used in this study a questionnaire. Result : The results of statistical tests chi-square test, p value = 0.014 was obtained. P value <0.05, it indicates there is a relationship of knowledge with the attitude of health workers in health centers BLS Pancur Stone. Conclusion : Expected to health workers in health centers Pancur stone to further improve and understand basic life support and can take action BLS in the treatment of patients who suffered sudden cardiac arrest, so handled quickly and accurately, as well as a training / seminar on basic life support on a regular basis.